Binding of Escherichia coli heat-stable enterotoxin to rat intestinal cells and brush border membranes. - Frantz, J C (1984)
The association of heat-stable enterotoxin (STa) produced by enterotoxigenic Escherichia coli 431 with isolated rat intestinal epithelial cells and brush border membranes was characterized. Specific binding of strain 431 125I-STa to a single class of specific high-affinity receptors was saturable and temperature dependent and reached a maximum between 5 and 10 min. A 1,000-fold excess of unlabeled 431 STa competitively displaced 90 to 95% of radiolabeled enterotoxin bound to brush border membranes. In contrast, specific binding of 431 125I-STa to intestinal cells ranged from 40 to 65%. The number of STa-specific receptors on rat intestinal cells determined by Scatchard analysis was 47,520 +/- 14,352 (mean +/- standard error of the mean) per cell, with affinity constants (KaS) of 2.55 X 10(11)and 4.32 x 10(11) liters/mol determined for intestinal cells and brush border membranes, respectively. Villus intestinal cells appeared to possess about twice as many STa receptors as did crypt cells. Dissociation of specifically bound 431 125I-STa from intestinal cells and brush border membranes was minimal (2 to 5%). In addition, neither the rate nor the extent of dissociation was increased by a 1,000-fold excess of unlabeled homologous 431 Sta. Binding experiments with 431 125I-STa and brush border membranes showed that purified unlabeled STas from enterotoxigenic E. coli strains 667 (class 1 porcine enteropathogen), B-41 (bovine enteropathogen), and human strains 213C2 (Mexico) and 153961-2 (Dacca, Bangledesh) exhibited patterns of competitive inhibition similar to those of homologous unlabeled 431 STa (class 2 enteropathogen). A lipid extract which contained gangliosides and glycolipids exhibited dose-dependent competitive inhibition of heat-labile enterotoxin binding to brush border membranes but did not inhibit binding of 431 125I-STa. Purified heat-labile enterotoxin from strain 286C2 did not inhibit binding of 431 STa to brush border membranes. Pronase treatment of brush border membranes reduced binding of 431 125I-STa by about 30%, suggesting that the STa receptor was a protein or a glycoprotein. The putative STa receptor was radiolabeled with 431 125I-STa and solubilized with sodium deoxycholate. One major radioactive band was detected by sodium dodecyl sulfate-polyacrylamide gel electrophoresis, followed by radioautography. These data suggested that STas bind essentially irreversibly to a specific receptor on the cell surface of intestinal cells before activation of guanylate cyclase.